METHOD FOR DETERMINING THE ORDER OF EXECUTION OF ASSAYS OF A SAMPLE IN A LABORATORY AUTOMATION SYSTEM - FRITCHIE, PATRICK P; JONES, JOHN CURTIS (2016)
A method for arranging assays in an order for execution in a system that employs a plurality of clinical analyzers, typically automated clinical analyzers. The method comprises the steps of (a) prioritizing the order of execution of a number of individual assays in a set of assays for a given sample in a sample container, the priority of an individual assay in the set of assays for the given sample being specified by the sensitivity of the individual assay, wherein there is at least one sample-to-sample carryover contribution from at least one other sample, an assay of the at least one other sample preceding the individual assay of the given sample; (b) comparing the sum of the sample-to-sample carryover contribution(s) from the at least one other sample for at least one assay of the at least one other sample that precedes the individual assay of the given sample to the sensitivity threshold of the individual assay of the given sample; and (c) using this comparison to determine whether to establish an order for the execution of assays for the given sample that includes the individual assay of the given sample or dispense at least a portion of the given sample into at least one additional container in order to carry out the assay.